Microorganisms present in southern brazilian handcrafted kombucha (Revista Contexto & Saúde, 2025)
Kombucha is a fermented beverage produced by a symbiotic culture of microbiologically active bacteria and yeast (SCOBY) with properties that are reportedly beneficial to health. A descriptive study was conducted with kombuchas produced on a small scale in Porto Alegre/RS. Samples were collected to isolate microorganisms present in the kombucha, as well as in the ingredients used (SCOBY and green tea). The beverages were analyzed in their original and flavored versions, with and without homogenization, in triplicate, totaling 12 samples. It was found that kombucha exhibited a high yeast count, with a significant difference in the beverage depending on homogenization, both in the homogenized original version (7.39±6.46 log CFU/mL vs. non-homogenized 6.46±5.39 log CFU/mL, p
Keywords: Camellia sinensis; Yeast; Fermented Beverages